Architectural Representation of Postcolonial in New Order Era Case Study: Padepokan Pencak Silat Indonesia - Novianti Mawar Sari; Kemas Ridwan Kurniawan (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
The aim and objective of this research is to elaborate on architectural representation in postcolonial practices in the New Order era. I describe the term postcolonial in this research as practices followed by leadership in society. The method of this research is using qualitative method with historical explanation starting from the architecture itself, then to the representation, space, nationalism, and power relations. The final of this research I explain with Padepokan Pencak Silat Indonesia as a case study in the New Order era. Later in this research I found that Padepokan Pencak Silat Indonesia proved to be an architectural representation in the New Order era with used the constructionist approach. I also mentioned in this research about the importance of power relations in the development of Padepokan Pencak Silat Indonesia with the contribution of those who have the authority to run the New Order era.